Effect of Covid-19 Vaccination on disease Severity among Covid-19 patients admitted in KMCTH - Mishra, Navin Kumar; Karn, Rohit; Shrestha, Milan; Acharya, Abhiskar; Acharya, Sunil; Dahal, Suresh; Neopane, Arpana (Nepalese Respiratory Journal, 2023)
Background: The COVID-19 Pandemic has affected millions of people globally with significant morbidity and mortality. Though the overall case fatality rate (CFR) in Nepal was less than 1% during the initial peak, the CFR is expected to increase during the current second wave of the pandemic. Since no specific effective therapies exist, breaking the chain of transmission sounds logical. COVID-19 vaccine development is believed to be effective and safe in preventing disease adverse outcomes. Aim: Primary aim of the study was to know the COVID-19 vaccination status among the patients admitted with RT-PCR positive for COVID-19 and secondary aim of the study was to observe the difference between the outcome in terms of resources utilization LIKE NON-INVASIVE VENTILATION (NIV), Hi-flow nasal cannula (HFNC) and invasive mechanical ventilation (IMV) in vaccinated and unvaccinated patients. Method: This was a hospital-based Prospective Observational Study. All patients admitted at KMCTH from June 01, 2021 –July 31st 2021 with COVID-19 RT-PCR Positive meeting inclusion criteria were enrolled. Ethical Clearance was taken from KMC-IRC. Result: During the study period, a total of 160 RT-PCR Positive Covid-19 cases were admitted at Kathmandu Medical College Teaching Hospital (KMCTH). Out of the total patients, 74 (46.25%) were not vaccinated for covid-19 whereas 86 (53.75%) patients were vaccinated either with Vero cell (39.53%) or Covishield (60.47%) Covid-19 vaccine. The study showed 2.32% of vaccinated patients required ventilatory support compared to 13.50 % of unvaccinated patients requiring ventilatory support having significant ( p value <0.05) impact on outcome. The relative risk for unvaccinated patients going to ventilator was 5.81 times higher than for vaccinated patients. Conclusion: The authors found out that more than half of the individual admitted were vaccinated (53.75 VS 46.25). Moreover, Vaccination (either with Covishield or Vero cell) appears to be effective in limiting requirement of more advance services like NIV, HFNC, and invasive mechanical ventilator. We recommend a larger, multicenter, randomized study in the future.